SINTESIS ASKORBIL PALMITAT DARI METIL PALMITAT DAN ASETIL ASKORBAT MELALUI REAKSI INTERESTERIFIKASI DENGAN KATALIS LIPASE DAN UJI AKTIVITAS ANTIOKSIDAN DENGAN METODE 2,2-diphenyl-1-picrylhidrazyl (DPPH) - Nisak, Khoirun; -, Daniel; Saleh, Chairul (Jurusan Kimia FMIPA UNMUL, 2017)
Synthesis of ascorbyl palmitate from methyl palmitate and acetyl ascorbate through interesterification reaction has been done. Modified were done to improve the nature of ascorbic acid that only soluble in water (lipophobic) become soluble in oil or fat (lipophylic). The interesterification reaction conducted with molar ratio 1:4 (methyl palmitate:acetyl ascorbate), lipase from coconut as a catalyst with amount 70 % from its substrat, pH 7, the temperature reaction 40-50 °C and the reaction time is 48 hours so the yield produce is 46,7241 %. Characterization of the functional group were confirmed with FT-IR. Analysis of antioxidant activity using radical reduction method 2,2-diphenyl-1-picrylhidrazyl (DPPH) result the antioxidant activity value of ascorbyl palmitate is 45,41 ppm. The result showing that ascorbyl palmitate synthesized is have a potency as an active antioxidant.